The observed diurnal cycle of low-level stratus clouds over southern West Africa: a case study - K. Babić; B. Adler; N. Kalthoff; H. Andersen; C. Dione; F. Lohou; M. Lothon; X. Pedruzo-Bagazgoitia (Atmospheric Chemistry and Physics, 2019)
This study presents the first detailed observational analysis of the complete diurnal cycle of stratiform low-level clouds (LLC) and involved atmospheric processes over southern West Africa (SWA). The data used here were collected during the comprehensive DACCIWA (Dynamics-Aerosol-Chemistry-Cloud-Interactions in West Africa) ground-based campaign, which aimed at monitoring LLC characteristics and capturing the wide range of atmospheric conditions related to the West African monsoon flow. In this study, in situ and remote sensing measurements from the supersite near Savè (Benin) collected during a typical day, which is characterized by the onset of a nocturnal low-level jet (NLLJ) and the formation of LLC, are analyzed. The associated dynamic and thermodynamic conditions allow the identification of five different phases related to the LLC diurnal cycle: the stable, jet, stratus I, stratus II, and convective phases. The analysis of relative humidity tendency shows that cooling is a dominant process for LLC formation, which leads to a continuous increase in relative humidity at a maximum rate of 6 % h−1, until finally saturation is reached and LLC form with a cloud-base height near the height of NLLJ maximum. Results of heat budget analysis illustrate that horizontal cold-air advection, related to the maritime inflow, which brings the cool maritime air mass and a prominent NLLJ wind profile, has the dominant role in the observed strong cooling of −1.2 K h−1 during the jet phase. The contribution from horizontal cold advection is quantified to be up to 68 %, while radiative cooling and sensible heat flux divergence both contribute 16 % to the observed heat budget below the NLLJ maximum. After the LLC form (stratus phases I and II), turbulent mixing is an important factor leading to the cooling below the cloud base, while strong radiative cooling at the cloud top helps to maintain thick stratus.